Media Belajar Matematika Berbasis Multimedia Interaktif dengan Pendekatan Contextual Teaching and Learning - Siamy, Lailatul; Farida, Farida; Syazali, Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2018)
The purpose of this study is to determine the response of students and the experts to multimedia-based interactive learning media with the approach of contextual teaching and learning (CTL) on wake-up space that has been developed. The method used in this research is 7 stages from 10 stages of development and development method from Borg and Gall which have been modified by sugiyono. The 7 stages are potential and problems, data collection, product design, product validation, design improvement, product testing and product revision. The instrument of data collection used is questionnaire of student response and material expert validation. Based on data analysis obtained from material experts and media experts stated that interactive multimedia-based learning media with contextual teaching and learning approach (CTL) is feasible to use, and data analysis obtained from students stated that interactive multimedia is very good. This means that interactive multimedia developed by researchers can be used as a learning resource for students of SMP / MTs class VIII